La influencia del rock en la creación de identidad cultural- nacional en los jóvenes de la ciudad de Latacunga - Córdova Taco, Carlos Alberto (2015)
This research was created to identify the rock as a creator of cultural-national identity in the youth of the Latacunga city, considering that the rock possesses a rich and vast history that involves not only the music itself but also involves customs, dress, identity and lifestyles, but in various sectors of society there is an unknowing, lack of understanding and acceptance to these ways of youth expression, making people fill with continued prejudice and misconceptions around the rockers….